2010
DOI: 10.1016/j.jacc.2010.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Consensus and Future Directions on the Definition of High On-Treatment Platelet Reactivity to Adenosine Diphosphate

Abstract: The addition of clopidogrel to aspirin treatment reduces ischemic events in a wide range of patients with cardiovascular disease. However, recurrent ischemic event occurrence during dual antiplatelet therapy, including stent thrombosis, remains a major concern. Platelet function measurements during clopidogrel treatment demonstrated a variable and overall modest level of P2Y(12) inhibition. High on-treatment platelet reactivity to adenosine diphosphate (ADP) was observed in selected patients. Multiple studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
858
1
43

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 1,073 publications
(925 citation statements)
references
References 96 publications
23
858
1
43
Order By: Relevance
“…4C, D, G, H, K, L). While IPA is clearly important, there is a growing consensus that residual high ontreatment platelet reactivity as reflected by maximal platelet aggregation with 5 μM ADP may be a more useful predictor of thrombotic risk (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4C, D, G, H, K, L). While IPA is clearly important, there is a growing consensus that residual high ontreatment platelet reactivity as reflected by maximal platelet aggregation with 5 μM ADP may be a more useful predictor of thrombotic risk (14).…”
Section: Discussionmentioning
confidence: 99%
“…However, the present randomised, double-blind, double-dummy study demonstrates that the terms "clopidogrel resistance" and "clopidogrel non-responsiveness" are inappropriate -because the residual platelet reactivity after clopidogrel treatment is in part unrelated to clopidogrel but is dependent on the pre-clopidogrel intrinsic variability in platelet activation. A preferred term is "high on-treatment platelet reactivity" (14,21,22). Indeed, a recent JACC white paper (14) concluded that the absolute level of platelet reactivity during clopidogrel treatment (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several risk stratification scores are available to assess the risk of recurrent ischemic events in ACS patients, such as GRACE (Global Registry of Acute Coronary Events), PURSUIT (Platelet Glycoprotein IIb/IIIa in Unstable Angina: Receptor Suppression Using Integrilin Therapy) and TIMI scores, none of these were used to identify and target those patients with ACS who were truly at high risk. Platelet function tests can also identify patients on clopidogrel at increased risk of MI, stent thrombosis, and cardiovascular death 34, 35. However, altering pharmacotherapy based on the results of platelet‐function testing failed to reduce recurrent ischemic events in patients undergoing PCI, including for ACS,36, 37 and current guidelines do not support platelet‐function testing 15, 38.…”
Section: Discussionmentioning
confidence: 99%
“…Essas drogas não devem ser suspensas nesse período pelo fato de proporcionar um maior risco de um novo evento tromboembólico, como uma trombose intra-stent (Abreu et al, 2007;Stone et al, 2007;King et al, 2008). A eficácia antiagregante dessas drogas pode ser avaliada por meio de testes de agregação plaquetária (Bonello et al, 2010;Breet et al, 2010;Sambu;Curzen, 2011 A este caso seguiram-se outros relatos de hemorragias pós-operatórias vinculadas ao uso do AAS (Thomason et al,, 1997;Foulke, 1976;Mc Gaul, 1978) e até de eventos hemorrágicos ligados apenas à sondagem periodontal (Schrodi et al, 2002).…”
Section: Introductionunclassified